Research on Green Innovation Spillover Effects of Peers Issuing Green Bonds: Evidence from China’s Green Bond Market - Qiankun Wang; Mingsheng Chen; Tingwen Liu (SAGE Open)
Green innovation plays a crucial role in fostering economic growth alongside environmental preservation. This study investigates the relationship between the issuance of green bonds and green innovation among peer companies, utilizing green patent data. The findings reveal that the issuance of green bonds significantly bolsters the level of green innovation among peer companies. Strategic innovation appears to be more pronounced than substantive innovation. The mechanism analysis indicates that the issuance of green bonds influences peer companies to engage in green innovation activities by alleviating their financing constraints and increasing their level of R&D investment. The heterogeneity analysis reveals that the impact of green bond issuance on green innovation among peer companies is particularly pronounced in capital-intensive companies and industries with high concentration. This study not only contributes evidence to the theory of “peer learning” but also provides a theoretical basis for expanding the economic benefits associated with green finance.